If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 12 = x + -9 Reorder the terms: 12 + -8x = x + -9 Reorder the terms: 12 + -8x = -9 + x Solving 12 + -8x = -9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + -8x + -1x = -9 + x + -1x Combine like terms: -8x + -1x = -9x 12 + -9x = -9 + x + -1x Combine like terms: x + -1x = 0 12 + -9x = -9 + 0 12 + -9x = -9 Add '-12' to each side of the equation. 12 + -12 + -9x = -9 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = -9 + -12 -9x = -9 + -12 Combine like terms: -9 + -12 = -21 -9x = -21 Divide each side by '-9'. x = 2.333333333 Simplifying x = 2.333333333
| 30=x+x*.05 | | B=2x+4 | | 9+6c=57 | | 5/9a=6=4/9a | | T^2+2t-17= | | 3d=7v | | 4+n=12n-9n-18 | | Log(5x+20)=2 | | 8+2x=180 | | 6b-1-10b=50 | | 6(1+10m)=5m+6 | | 5+x^10=17 | | 6x-10=4-2/3(6x-9) | | F(x)=-1x^2+6x+7 | | -28+6v=-6-2(-3v+11) | | 8y=-5+7x | | 6x-4i=3(2x-4u) | | 31+5x=33 | | 9n+2-7+5=3n-5n | | (2x+1)(10-3x)=0 | | p=-2p+3 | | Sen(7x)+Sen(3x)+2sen^2x=1 | | y=(x-7)(x+5) | | 5x^2-12x+16=0 | | 4w^5-22w^4-12w^3= | | Sen(7x)+Sen(3x)+2senx^2=1 | | 7x+5=10(x+7)-3x | | 2.9x-15.17=3.1 | | a*a+a-56=0 | | 6v-4v+10=2v-10 | | 92=9x+2 | | 17-4logx=25 |